Limitations of human tau-expressing mouse models and novel approaches of mouse modeling for tauopathy - Sahara, Naruhiko; Yanai, Rin (Frontiers in Neuroscience, 2023)
Neurofibrillary tangles (NFTs) composed of hyperphosphorylated tau protein are primarily neuropathological features of a number of neurodegenerative diseases, collectively termed tauopathy. There is no disease-modifying drug available for tauopathy except anti-amyloid antibody therapies for Alzheimer’s disease. For tau-targeting therapy, experimental models recapitulating human tau pathologies are indispensable. However, there are limited numbers of animal models that display intracellular filamentous tau aggregations. At present, several lines of P301L/S mutant tau-expressing transgenic mice successfully developed neurofibrillary pathology in the central nervous system, while most non-mutant tau-expressing transgenic mice rarely developed tau pathology. Importantly, recent studies have revealed that transgenes disrupt the coding sequence of endogenous genes, resulting in deletions and/or structural variations at the insertion site. Although any impact on the pathogenesis of tauopathy is unknown, gene disruptions may affect age-related neurodegeneration including tangle formation and brain atrophy. Moreover, some mouse lines show strain-dependent pathological features. These limitations (FTDP-17 mutations, insertion/deletion mutations, and genetic background) are a major hindrance to the establishment of a precise disease model of tauopathy. In this review, we noticed both the utility and the pitfalls of current P301L/S mutant tau-expressing transgenic mice, and we propose future strategies of mouse modeling to replicate human tauopathies.